Malaysia: PM Abdullah Badawi’s Performance and Prospects - Mushahid Ali (2016)
Malaysian Prime Minister Abdullah Ahmad Badawi completes four months in office with a sense of satisfaction that he has established his hold on the reins of power and is now ready to put his own stamp on the government and become the leader of the main ruling party, UMNO, in his own right. This “feel good” factor has spurred UMNO and the National Front (BN) to put into high gear their preparations for the nation-wide parliamentary and state elections, which must be held by November 2004. They have the renewed confidence of a comfortable victory, retaining BN’s two-thirds majority in Parliament and to regain some of the seats lost in the Malay-dominated constituencies in Northern Peninsular Malaysia at the 1999 elections, particularly in Kedah and even Terengganu, which, along with Kelantan, is under the control of the Pan-Malaysian Islamic Party, PAS.